Impact of OHS and leadership style on employee performance with job satisfaction as a mediator - Hallaludin, M Artha; Suhada, Suhada; Nasrulloh, Rifqi Syarif (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study examines the influence of occupational health and safety (OHS) practices and leadership behavior on workforce performance at PT IB, with job satisfaction investigated as a potential mediating factor. Using a quantitative approach, data were collected through structured questionnaires and analyzed to assess these organizational relationships. The findings reveal that OHS practices significantly enhance both employee performance and job satisfaction. At the same time, leadership behavior positively affects job satisfaction but does not directly impact performance. Contrary to expectations, job satisfaction does not mediate the relationship between OHS, leadership, and performance outcomes. These results underscore the critical role of robust OHS implementation and practical leadership approaches in fostering workforce satisfaction and productivity. These findings underscore the crucial role of robust OHS implementation and practical leadership approaches in boosting workforce satisfaction and productivity. Organizational management should therefore prioritize workplace safety and leadership development as key drivers of employee performance.